2014
DOI: 10.1007/s40477-014-0132-3
|View full text |Cite
|
Sign up to set email alerts
|

Diagnosis of one small bowel tumor: the role of conventional ultrasound and elastography

Abstract: Neuroendocrine tumors are the most common primary tumors of the small bowel, but diagnosis is usually delayed as the lesions are small and symptoms are mild or nonspecific. Diagnosis of this disease is currently based on radiologic or endoscopic findings. Ultrasound (US) is used as a first-line examination in patients with abdominal symptoms, as this technique permits an overall view of the gastrointestinal tract providing diagnosis of inflammatory and/or neoplastic disorders in a large proportion of patients.… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2017
2017
2019
2019

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(4 citation statements)
references
References 4 publications
0
4
0
Order By: Relevance
“…The introduction of dedicated US software for elastographic assessments would greatly improve the diagnostic potential of CEUS for assessing bowel wall fibrosis grade in patients with CD [78][79][80][81].…”
Section: Ceusmentioning
confidence: 99%
“…The introduction of dedicated US software for elastographic assessments would greatly improve the diagnostic potential of CEUS for assessing bowel wall fibrosis grade in patients with CD [78][79][80][81].…”
Section: Ceusmentioning
confidence: 99%
“…Recently, SE or SWE has been suggested as an adjunct tool for assessing GI diseases [1517]. However, the data is still limited at transabdominal elastography [11, 18]. Previous study reported that gastric GIST was a harder tumor than other SMTs in EUS elastography [7].…”
Section: Discussionmentioning
confidence: 99%
“…Tsuji et al reported that EUS-elastography could be used to differentiate gastric GISTs with other SMTs because of its stiffness [7]. Few data exists regarding transabdominal elastography for SB GISTs [11].…”
Section: Introductionmentioning
confidence: 99%
“…Conventional ultrasound (US) examination has become one of the preferred imaging examination methods of thyroid disease, but thyroid diseases are complex and diverse; in the two-dimensional ultrasonogram, there are overlapping benign and malignant nodules, and some nodules have the features of both benign nodular and malignant nodules, known as an uncertain nodule and it is difficult to determine its nature only from the ultrasonogram, so there are still some limitations on its differential diagnosis, directly affecting the choices of clinical treatment and surgical methods, which requires the physicians to make a preliminary qualitative diagnosis of lesions, so as to provide the reference basis for clinicians ( 1 4 ).…”
Section: Introductionmentioning
confidence: 99%